Analysis of Accounting Information on Investment Decision Making at PT. MNC Sekuritas Manado - Tabe, Ridwan; Syarifuddin, Syarifuddin; Anggrayni, Lilly (Jurnal Ekonomi Balance, 2023)
This study investigates the influence of accounting information on investment decisions within the capital market, focusing on PT. MNC Sekuritas Manado. Employing a quantitative approach and simple regression analysis using SPSS version 25.0, data was collected through questionnaires distributed to 119 investors. The research validated and ensured the reliability of instruments through validity and reliability tests, while normality tests confirmed the normal distribution of variables. Results indicate a significant 53.6% impact of accounting information on investment decisions. Investors, particularly in PT. MNC Sekuritas Manado, rely on fundamental information, emphasizing financial reports, to inform their investment decisions. The study contributes to the signaling theory, emphasizing the crucial role of accounting information as a powerful signal for investors. Practical implications highlight the importance for companies to enhance the quality and transparency of accounting information, facilitating more informed investment decisions by investors. Recommendations include expanding future research to encompass a larger sample size, conducting comparative analyses among companies with varying financial performances, and considering additional external factors influencing investment decisions. This research contributes to a more comprehensive understanding of how accounting information shapes investment decisions in the dynamic context of the capital market. The findings provide valuable insights for companies, investors, and policymakers aiming to improve transparency and decision-making processes within the financial landscape.